Interference with Lipoprotein Maturation Sensitizes Methicillin-Resistant Staphylococcus aureus to Human Group IIA-Secreted Phospholipase A2 and Daptomycin - Marieke M. Kuijk; Yongzheng Wu; Vincent P. van Hensbergen; Gizem Shanlitourk; Christine Payré; Gérard Lambeau; Sandra Man-Bovenkerk; Jennifer Herrmann; Rolf Müller; Jos A.G. van Strijp; Yvonne Pannekoek; Lhousseine Touqui; et al. (Karger Publishers, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) has been classified as a high priority pathogen by the World Health Organization underlining the high demand for new therapeutics to treat infections. Human group IIA-secreted phospholipase A2 (hGIIA) is among the most potent bactericidal proteins against Gram-positive bacteria, including S. aureus. To determine hGIIA-resistance mechanisms of MRSA, we screened the Nebraska Transposon Mutant Library using a sublethal concentration of recombinant hGIIA. We identified and confirmed the role of lspA, encoding the lipoprotein signal peptidase LspA, as a new hGIIA resistance gene in both in vitro assays and an infection model in hGIIA-transgenic mice. Increased susceptibility of the lspA mutant was associated with enhanced activity of hGIIA on the cell membrane. Moreover, lspA deletion increased susceptibility to daptomycin, a last-resort antibiotic to treat MRSA infections. MRSA wild type could be sensitized to hGIIA and daptomycin killing through exposure to LspA-specific inhibitors globomycin and myxovirescin A1. Analysis of >26,000 S. aureus genomes showed that LspA is highly sequence-conserved, suggesting universal application of LspA inhibition. The role of LspA in hGIIA resistance was not restricted to MRSA since Streptococcus mutans and Enterococcus faecalis were also more hGIIA-susceptible after lspA deletion or LspA inhibition, respectively. Overall, our data suggest that pharmacological interference with LspA may disarm Gram-positive pathogens, including MRSA, to enhance clearance by innate host defense molecules and clinically applied antibiotics.